2022
DOI: 10.1002/adhm.202201441
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Upregulation of HSP70 by Metal‐Organic Frameworks Nanoamplifier for Enhanced Microwave Thermal‐Immunotherapy

Abstract: Thermotherapy can directly kill tumor cells whilst being accompanied by immune‐enhancing effects. However, this immune‐enhancing effect suffers from insufficient expression of immune response factors (e.g., heat shock protein 70, HSP70), resulting in no patient benefiting due to the recurrence of tumor cells after thermotherapy. Herein, a nanoengineered strategy of programmed upregulating of the immune response factors for amplifying synergistic therapy is explored. Metal‐organic frameworks nanoamplifiers (tep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, there has been a growing emphasis on combination therapy strategies, which hold the promise of achieving additive and/or synergistic antitumor effects by integrating two or more treatment modalities. [176,177] The versatility of design, synthesis, and modification options of ZIF-8 make it as highly DOX@ZIF-8 Dox Chemotherapy [154] RhB@ZIF-8 Rhodamine B (RhB) ATP Sensing [155] ZIF-8@Ce6-HA Ce6 PDT [77] Bi@ZIF-8 Bi PTT [156] HZ@GD DNAzyme down-regulate GLUT1 expression [157] ZIF-8/DOX@ZrO 2 @IL DOX, ZrO 2 , IL Chemo-microwave Thermal therapy [158] BSA-MnO 2 / Ce6@ZIF-8…”
Section: Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there has been a growing emphasis on combination therapy strategies, which hold the promise of achieving additive and/or synergistic antitumor effects by integrating two or more treatment modalities. [176,177] The versatility of design, synthesis, and modification options of ZIF-8 make it as highly DOX@ZIF-8 Dox Chemotherapy [154] RhB@ZIF-8 Rhodamine B (RhB) ATP Sensing [155] ZIF-8@Ce6-HA Ce6 PDT [77] Bi@ZIF-8 Bi PTT [156] HZ@GD DNAzyme down-regulate GLUT1 expression [157] ZIF-8/DOX@ZrO 2 @IL DOX, ZrO 2 , IL Chemo-microwave Thermal therapy [158] BSA-MnO 2 / Ce6@ZIF-8…”
Section: Cancer Therapymentioning
confidence: 99%
“…Therefore, there has been a growing emphasis on combination therapy strategies, which hold the promise of achieving additive and/or synergistic antitumor effects by integrating two or more treatment modalities. [ 176,177 ] The versatility of design, synthesis, and modification options of ZIF‐8 make it as highly promising candidate in combination therapies. Below, we summarize the application of ZIF‐8 in multi‐modal synergistic anticancer therapies.…”
Section: Application Of Zif‐8mentioning
confidence: 99%
“…The subsequent immune cascade (enhanced CTL infiltration) events further cooperated with PT and FT, enabling PCSFG to completely eradicate primary 4T1 tumors (TIR = 100%) and reject re-attacked 4T1 tumors. Furthermore, NO-induced ICD can play multiple antitumor effects in conjunction with other therapies such as PDT, [118,189,190] RT, [11d] PTT, [191][192][193][194] CT, [196] which provides new inspiration for promoting more synergetic therapy strategies based on IT.…”
Section: Inducing Icdmentioning
confidence: 99%
“…NanoNO* [ 188] N-nitrosamine PDT RO/NS NG [189] Endogenous nitrite IT, PDT BP@Ec-T [190] L-Arg PDT L-Arg/MB@MP [118] L-Arg RT ACSL-A [11d] RSNO CDT, PTT, IT PCSFG [ 191] L-Arg PTT, CT LA-CaO 2 @PDA [192] RSNO PTT GCZMT [ 193] L-Arg PTT GO-Arg-SL [194] RONO 2 ∖ D-KLP 22 ONSs [ 195] L-Arg CT Ang-PAMSe/TLND [ 196] Regulating immune cells RSNO CTLs activation, Tregs inhibition IT BMS-SNAP-MOF [ 197] RSNO RT, IT Ag 2 S@BSA-SNO [198] L-Arg CT, SDT L-ARG@PTX [158] SNP RT, IT ZnNO( 32 P) [ 199] L-Arg IT Mon@LA-PDE5i@M ATVs [ 200] Furoxans IT S-LFO [11b] DNIC ∖ CXCR4-targeted-LCP-NONPs [ 201] PDE5i IT, SDT ICG/PDE5i/FRMON [ 202] RSNO TAM repolarization ∖ APAP-P-NO [203] RSNO ∖ DMON-SNO [ 91] Endogenous nitrite SDT R@HTR [204] L-Arg Catalytic therapy D/L-Arginine@Ru [ 205] Down regulating PD-L1 expression RSNO Hypoxia relief PTT, IT RBCm/PAAV-SNO/IR1061+1-MT NP [206] RONO 2 PTT NOPS@BP [207] DNIC Transcription inhibition ∖ NanoNO [ 13b] L-Arg Not mention PTT, PDT Catalytic therapy M@BPAG [208] RONO 2 Not mention IT UNTPs [ 209] *NanoNO refers to Jiang's [ 188] research, NanoNO refers to Sung's [ 13b] research.…”
mentioning
confidence: 99%
“…Recently, improving the pharmacokinetics and biological distribution of anticancer drugs has been greatly promoted by the construction of various nano-delivery systems. ,, A metal–organic framework (MOF) is a kind of network structure of porous materials formed by inorganic metal nodes (metal ions or oxide clusters) and organic connectors self-assembly. Compared with traditional nanocarriers, MOFs have unique characteristics such as high porosity, large specific surface area, tuneable pore size, structural stability, less toxicity, and better biocompatibility. MOF nanoparticles can also be explored as potential catalysts for anticancer photodynamic and chemodynamic therapy. , Previous studies have found that some specific MOFs can be designed to not only improve the efficacy of MW hyperthermia by promoting heat generation efficiency but also exhibit non-thermal MW dynamic therapy by improving the concentration of cytotoxic ROS in tumors. , Moreover, researchers have found that ROS can inhibit the expression of PKM2 in tumor cells, thereby inhibiting glycolysis . Motivated by these recent advances, we here proposed the construction of the SK-loaded MOF delivery system for efficient MW hyperthermia.…”
Section: Introductionmentioning
confidence: 99%